(untitled) (Plant Tissue Culture and Biotechnology, 2017)
Genetic variability of tropical strawberry genotypes was determined through Ramdom Amplified Polymorphic DNA (RAPD) primers. Out of 14 RAPD primers six showed reproducible and polymorphic bands. The results revealed that the maximum polymorphic bands were produced by the primer OPB 12. Ten genotypes were differentiated into two clusters on the basis of Unweighted Pair Group Method With Arithmetic Averages (UPGMA). Genotypic variation based on molecular characterization indicated that genotypes belonging to two different clusters depend on their genetic component. So, selection of parents from different clusters will provide the maximum heterosis in yield. Plant Tissue Cult. & Biotech. 27(1): 33-39, 2017 (June)